Single Center Experience of Cell‐Free and Concentrated Ascites Reinfusion Therapy in Malignancy Related Ascites. Issue 1 (17th April 2013) - Ito, Tetsuya; Hanafusa, Norio; Fukui, Mieko; Yamamoto, Hiroko; Watanabe, Yasuyuki; Noiri, Eisei; Iwase, Satoru; Miyagawa, Kiyoshi; Fujita, Toshiro; Nangaku, Masaomi
Abstract Cell‐Free and Concentrated Ascites Reinfusion Therapy (CART) is expected to improve patients' symptoms related to ascites. Use of a patient's own proteins in ascites might reduce the risk of infection. However, several reports have described that reinfusion of concentrated ascites might elevate body temperature. The aim of this study is to examine the safety and efficacy of the CART system performed exclusively on patients with malignancies. In this retrospective cohort observational study, we examined 81 CART processes performed on 24 patients with malignancies. Data were collected from medical records and records during processing of ascites. We investigated the effectiveness and adverse events during the procedures. The amount of ascites processed was 2.6 ± 1.4 L on average. The concentration ratio was 9.31 ± 5.45 on average. We found an increase in the urine volume after the procedure, which was significantly related to the amount of reinfused protein. The body temperature increased by 0.44°C. Systolic blood pressure decreased by 4 mm Hg after paracentesis, but no significant difference was found between the pressure before paracentesis and after reinfusion. In platelet counts, no significant change was observed. After all, no clinically significant adverse event was confirmed during CART procedures. Results show that CART can be performed safely even on patients with malignancy‐related ascites and that the procedure might improve diuresis.